2017
DOI: 10.1016/j.maturitas.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Hot flashes and midlife symptoms in relation to levels of salivary cortisol

Abstract: Objectives This study examined the relationship between salivary cortisol levels and hot flashes during midlife. Previous studies have shown that cortisol levels increase with hot flashes in the laboratory, and higher cortisol levels have been associated with more severe hot flashes. Salivary cortisol levels were also examined in relation to total number of midlife symptoms. Methods Women aged 40-60 years (n=109) reported the presence or absence of 23 symptoms, including hot flashes, during the previous 2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…For all this trouble, these methods still lack standardization, accuracy and precision ( Ceglarek et al, 2010 ; Rosner et al, 2013 ; Stanczyk & Clarke, 2014 ; Wang et al, 2016 ), so optimal means of studying menopause in autism require further thought and discussion. Some studies have linked menopausal symptoms and distress to cortisol, adrenaline and noradrenaline, associated with the HPA axis and the autonomic nervous system, respectively ( Gerber et al, 2017 ; Reed et al, 2016 ; Woods et al, 2014 ). Cortisol levels are robustly related with mental and physical health outcomes ( Adam et al, 2017 ), so this may also be a worthy physiological index to compare between groups and examine alongside symptom-reporting, given that (a) physical and mental health often decrease with menopause in the non-autistic population ( Hoyt & Falconi, 2015 ), and (b) autistic people are already vulnerable to increased morbidity and mortality ( Croen et al, 2015 ; Hirvikoski et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…For all this trouble, these methods still lack standardization, accuracy and precision ( Ceglarek et al, 2010 ; Rosner et al, 2013 ; Stanczyk & Clarke, 2014 ; Wang et al, 2016 ), so optimal means of studying menopause in autism require further thought and discussion. Some studies have linked menopausal symptoms and distress to cortisol, adrenaline and noradrenaline, associated with the HPA axis and the autonomic nervous system, respectively ( Gerber et al, 2017 ; Reed et al, 2016 ; Woods et al, 2014 ). Cortisol levels are robustly related with mental and physical health outcomes ( Adam et al, 2017 ), so this may also be a worthy physiological index to compare between groups and examine alongside symptom-reporting, given that (a) physical and mental health often decrease with menopause in the non-autistic population ( Hoyt & Falconi, 2015 ), and (b) autistic people are already vulnerable to increased morbidity and mortality ( Croen et al, 2015 ; Hirvikoski et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Not all studies have shown a consistently positive relationship between hot flashes and cortisol levels. For example, hot flash report has not been associated with the cortisol awakening response or diurnal variation in cortisol levels [26, 28, 29]. One study found greater self-reported hot flash severity associated with a flatter diurnal slope in salivary cortisol [30].…”
Section: Introductionmentioning
confidence: 99%
“…The Neighborhood Study of Blood Pressure and Sleep, conducted from September 1999 through July 2003, was a cross-sectional investigation of race/ethnicity, socioeconomic status, and diurnal blood pressure (BP) patterns [18, 51]. Data for this study were drawn from this parent study.…”
Section: Methodsmentioning
confidence: 99%